Social isolation as a predictor for depressive symptoms among college students: The moderating role of future orientation - Ramos, Rad Jasper L. (Animo Repository, 2021)
The COVID-19 pandemic quarantine forced a new normal, initiating the use of online means to connect, communicate and interact. When access becomes limited, people may feel socially isolated, leading to experiencing some depressive symptoms. In this study, the researchers aim to determine whether high levels of social isolation is a predictor for depressive symptoms, thus, attempts to discover whether future orientation could serve as a moderator between the relationship of the two variables within the context of the COVID-19 pandemic quarantine. To do so, the researchers have employed a quantitative study of 186 college students, ages 18 to 24, currently residing in the Philippines. The time perspective theory was used as the framework to account for results on future orientation. The survey materials included were the Lubben Social Network Scale Revised (LSNS-R), Center for Epidemiologic Studies Depression (CES-D), and Future Time Perspective (FTP). A moderation analysis through Jamovi software was used in analyzing results from this study. Findings showed that social isolation predicted depressive symptoms, but future orientation had no moderating effect between the variables. The implications of this research can be useful in reducing the severity of depressive symptoms by facilitating future-oriented thinking.